Efficacy of radio-hyperthermo-chemotherapy as salvage therapy for recurrent or residual malignant soft tissue tumors. (1st January 2019) - Aiba, Hisaki; Yamada, Satoshi; Mizutani, Jun; Yamamoto, Norio; Okamoto, Hideki; Hayashi, Katsuhiro; Takeuchi, Akihiko; Miwa, Shinji; Higuchi, Takashi; Abe, Kensaku; Taniguchi, Yuta; Tsuchiya, Hiroyuki; et al.
Abstract: Background: Recurrence after wide excision or residual tumor after an unplanned excision of a malignant soft tissue sarcoma (STS) is a complex problem, due to a higher recurrence rate and poorer survival rate compared with primary resection. Regional hyperthermia was used, with the expectation that it will enhance the anti-tumor effects of chemotherapy and radiotherapy. This study aimed to assess the efficacy of neoadjuvant concomitant radiotherapy, hyperthermia, and chemotherapy (RHC) for salvage of recurrent or residual malignant STS. Methods: We identified 64 patients with recurrent or residual STS treated between 1994 and 2013. After excluding those with low-grade malignancy, with recurrent bone tumor in the soft tissues, with truncal STS, and who declined to participate, 23 patients (7 with recurrence and 16 with residual tumor) underwent RHC. The histologic diagnoses were undifferentiated pleomorphic sarcoma ( n  = 11), synovial sarcoma ( n  = 3), leiomyosarcoma and myxoid liposarcoma ( n  = 2 each), and other histologic types. As primary outcomes, the 5-year overall survival (OS), distant metastasis-free survival (D-MFS), and local control (LC) rates were evaluated by Kaplan-Meier analysis. Results: The median follow-up period was 112.3 months. The 5-year OS, D-MFS, and LC were 86.4%, 77.4%, and 86.7%, respectively. In the univariate analysis, tumor depth was considered as a negative prognostic factor for OS and D-MFS, and a positive margin was also a negative prognostic factor for OS, D-MFS LC with retained on Cox proportional hazards model in OS, and D-MFS. Conclusion: RHC is an effective option for salvage treatment of recurrent and residual STS.